Bahasa Inggris Bahasa Inggris: Bahasa Inggris - Putra, I Putu Hendra Airlangga; Utami, Anak Agung Istri Dewi Adhi; Suastika, I Nengah (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
This study aims to describe how the film Two Blue Lines can be optimized as a sex education medium to form honest characters in adolescents. Lack of knowledge about sexuality makes adolescents vulnerable to risky behaviors such as premarital sexual relations and early marriage. The study uses a qualitative descriptive approach with the subjects of SMA Negeri 1 Singaraja students. Data were collected through observation, interviews, and literature studies. The results show that the film Two Blue Lines is able to attract students' interest, provide a new understanding of the risks of sexual behavior, and instill the value of honesty through story conflicts that are close to their lives. The discussion after the screening encourages students to have the courage to speak their minds and understand the importance of honesty. Thus, the optimization of film media can be an alternative learning strategy that is interesting, contextual, and supports character education and sex education in schools.